PENGARUH ATRIBUT PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN KONSUMEN PRODUK SMARTPHONE - Firmansyah, Rezza; Restuti, Sri; Noviasari, Henni (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Currently, the most widely used technology that can support these needs is one of them in the form of smartphone products or better known as smartphones. Consumers will be faced with information about a product in making purchasing decisions. This study aims to determine the effect of product attributes and prices on purchasing decisions and consumer satisfaction of Xiaomi smartphone products in Pekanbaru City. The population in this study is the people of Pekanbaru City who buy and use Xiaomi smartphones. The sampling technique used purposive sampling method and 108 people were selected as samples. Structural Equation Modeling with SmartPLS 3 software was used as a data analysis method. The results showed that product attributes have a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, and purchase decisions have a positive and significant effect on consumer satisfaction.